PROCEDURAL SUCCESSION CONCEPT AND BASES OF PROCEDURAL SUCCESSION - Mamuka Ghviniashvili (European Scientific Journal, ESJ, 2013)
Under the Article 92, part one, of the Civil Procedural Code of Georgia, if one of the parties withdraws from a disputed legal relationship or from the legal relationship established by a court decision (citizen’s death, reorganization of a legal person, concession of claim, and assignment of debt), the court shall allow substitution of that party with its legal assignee. Legal assignment is allowed on any stage of proceeding.